Loyalty - Scottoline, Lisa; Ballerini, Edoardo, 1970- ([New York] : Penguin Audio, 2023)
Franco Fiorvanti is a handsome lemon grower toiling on the estate of a baron. He dreams of owning his own grove, but the rigid class system of Sicily thwarts his ambition. Determined to secure a better future, Franco will do anything to prove his loyalty to the baron. But when the baron asks him to kidnap a little boy named Dante, Franco makes a decision that will change his life--and even the history of Sicily--forever.
Keywords: Orchards -- Fiction. -- Italy; Nobility -- Fiction. -- Italy; Kidnapping -- Fiction; Mafia -- Fiction; Organized crime -- Fiction; FICTION / Historical / General; FICTION / Thrillers / Crime; FICTION / World Literature / Italy; Sicily (Italy) -- Fiction; Audiobooks; Thrillers (Fiction); Suspense fiction; Historical fiction; Historical fiction; Novels